Exploring the Role of Financial Knowledge on the Economic Empowerment and Poverty Alleviation among Women Entrepreneurs in KwaZulu-Natal, South Africa - Kandolo, Ka Muzombo; Ngibe, Musawenkosi (Business, Management and Economics: Research Progress Vol. 9, 2024)
Aims: The study examines the extent to which financial knowledge influences the economic empowerment of women entrepreneurs in Durban, South Africa. Study Design: This study adopted a survey research design. Place and Duration of Study: Data was collected from women entrepreneurs based in the Durban Central Business District, South Africa, during the period from May to July 2019. Methodology: The study employed a quantitative research strategy grounded in a positivist paradigm. Data was collected from 400 women entrepreneurs using a convenience quota sampling technique, with the sample size determined through the Cochran formula. A total of 500 surveys were distributed, yielding 400 completed responses and an 80% response rate. Data analysis involved descriptive statistics, Spearman's rho, and Chi-square tests, all conducted using the Statistical Package for the Social Sciences (SPSS). Results: The study aimed to examine whether there is a positive relationship between the perceived link between economic empowerment and gender equality, and the perception of financial knowledge's role in poverty alleviation. Additionally, it sought to determine whether a positive relationship exists between perceived managerial control over loans and the perception of financial knowledge's role in alleviating poverty. Conclusion: The study aimed to explore the need for financial knowledge and economic empowerment, specifically examining how financial literacy can play a pivotal role in poverty alleviation. The findings highlighted that a significant gap exists in financial knowledge among disadvantaged communities, where individuals often lack the necessary understanding to make informed financial decisions. This lack of knowledge exacerbates their economic challenges, making it more difficult for them to escape the cycle of poverty. Moreover, the study emphasized that economic empowerment, facilitated by financial education, is essential for fostering long-term economic independence. It is evident that when women entrepreneurs are equipped with essential financial skills, such as budgeting, saving, and investing, they are better positioned to improve their financial stability and create opportunities for sustainable growth.